Penerapan Literasi Digital dan Seni Berbahasa di Kalangan Remaja Masjid Bustanul Ibad Bekasi - Ramdhania, Khairunnisa Fadhilla; Setiawati, Siti; Khalida, Rakhmi; Kustanto, Prio Kustanto; Insan, Insan (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
In 2022, Indonesia is still overshadowed by the covid-19 pandemic. Moreover, this covid-19 has a new variant called covid-19 Omicron. Covid-19 Omicron in Indonesia continues to increase. The Ministry of Health predicts that the addition of Covid-19 Omicron cases in Indonesia is expected to continue until it reaches its peak in February 2022. For this reason, some parts of the education world in Indonesia are still carrying out online learning. Because of concerns about this omicron wave, the Three Pillars of Higher Education, were carried out online with the object of research being the youth of mosques in North Bekasi. The purpose of this socialization is to provide information and descriptions of positive and negative things or the impacts resulting from the development of digital literacy and teach them about the art of good language when they have to appear in public. The method used is to provide webinars/socialization on digital literacy and good language arts among mosque youths.